2017
DOI: 10.1016/j.avsg.2016.08.005
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of Critical Limb Ischemia in an Urban, Safety Net Hospital Population with High WIfI Amputation Scores

Abstract: Background Patients presenting to a public hospital with critical limb ischemia (CLI) typically have advanced disease with significant comorbidities. The purpose of this study was to assess the influence of revascularization on 1-year amputation rate of CLI patients presenting to Los Angeles County USC Medical Center, classified according to the Society for Vascular Surgery Wound, Ischemia and foot Infection (WIfI). Methods A retrospective review of patients who presented to a public hospital with CLI from F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
44
1
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 58 publications
(52 citation statements)
references
References 15 publications
(21 reference statements)
2
44
1
2
Order By: Relevance
“…Diabetic foot ulcers are a major complication of diabetes, and timely healing of these ulcers is important . However, measures of healing rate may not provide a complete indication of the effectiveness of overall management of diabetic foot ulcers because of high recurrence rates.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Diabetic foot ulcers are a major complication of diabetes, and timely healing of these ulcers is important . However, measures of healing rate may not provide a complete indication of the effectiveness of overall management of diabetic foot ulcers because of high recurrence rates.…”
Section: Discussionmentioning
confidence: 99%
“…Diabetic foot ulcers are a major complication of diabetes, and timely healing of these ulcers is important. 9 However, measures of healing rate may not provide a complete indication of the effectiveness of overall management of diabetic foot ulcers because of high recurrence rates. The most important outcome for patients is to remain ulcer-free, yet these ulcer-free survival days have hardly been investigated since they were first introduced.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…7,8 This article will focus on endovascular therapies.Wound-healing and limb-salvage in LTI is multifactorial, but revascularization is critical. [9][10][11][12] There is no absolute perfusion target threshold, making goals of revascularization difficult to define. A recent review found that skin perfusion pressure ≥ 25 mm Hg, toe pressure ≥ 30 mm Hg and a transcutaneous pressure 702169D STXXX10.1177/1932296817702169Journal of Diabetes Science and TechnologyChung…”
mentioning
confidence: 99%